2019
DOI: 10.5010/jpb.2019.46.1.045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biological activity for Dangyuja (Citrus grandis) leaves and investigation of optimal concentrations extracted by alternative ethanol concentrations

Abstract: The Citrus grandis Osbeck is a special product in the Jeju island. The product has been as a remedy for liver damage and hang over. This study demonstrates how to investigate and compare the antioxidant, phenol content, tyrosinase and α-glucosidase inhibitory activity, antimicrobial, and alcohol dehydrogenase (ADH) and acetaldehyde dehydrogenase (ALDH) activity with the C. grandis leaves extracted in different ethanol concentrations. From the yield, a 20% ethanol extract demonstrated the highest results among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
0
1
Order By: Relevance
“…In exploring UAE conditions for maximum TAI, the maximum TAI conditions values were predicted to be 30.0 min, 26.3 °C, and 99.5%. This result is similar to that reported by Nakamura et al [ 31 ] In a study on biological activity of citron leaves, when 20.0%~80.0% of ethanol was used as an extraction solvent, TAI increased in proportion in response to the increase in ethanol concentration and showed maximum value in extraction using 80% ethanol. This suggests that using higher concentration of ethanol is advantageous in extracting bioactive compounds with skin-whitening effect from peanut shell or other plants.…”
Section: Resultssupporting
confidence: 91%
“…In exploring UAE conditions for maximum TAI, the maximum TAI conditions values were predicted to be 30.0 min, 26.3 °C, and 99.5%. This result is similar to that reported by Nakamura et al [ 31 ] In a study on biological activity of citron leaves, when 20.0%~80.0% of ethanol was used as an extraction solvent, TAI increased in proportion in response to the increase in ethanol concentration and showed maximum value in extraction using 80% ethanol. This suggests that using higher concentration of ethanol is advantageous in extracting bioactive compounds with skin-whitening effect from peanut shell or other plants.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, the minimum was observed at 20 °C/30 min/90% EtOH, which was 7.5% lower than the maximum. This finding exceeded that obtained by another study on optimizing extraction method (Nakamura et al, 2019 ). They found that extraction yield of plant extracts using ultrasonic extraction with on 0–100% ethanol was ranged 3.82 to 27.62% and was decreased to 3.82% on 100% ethanol extraction.…”
Section: Resultscontrasting
confidence: 71%
“…Flavonoid는 노란색이나 담황색을 나타내는 phenol계 화합물의 총 칭으로 (Hertog et al, 1993) 혈관 내에서 nitric oxide와 superoxide의 반응으로 생성되는 peroxynitrite와 그 전구체인 superoxide를 직접적 으로 제거해 주는 것으로 알려져 있다 (Heim et al, 2002). 이에 본 연 구에서는 재래종 대파의 부위별 열수추출물의 total flavonoid 함량을 분석하여 Table 1에 제시한 (Blois, 1958;Ju et al, 2009;Nakamura et al, 2019) Hyun & Han, 2014). 이는 α-glucosidase 저해제가 α-glucosidase에 경쟁적으로 결합하여 효소 활성을 억제하기 때문이 다 (Yong et al, 2011).…”
Section: ) Total Flavonoid 함량unclassified